Cohesion and Coherence in Reading Texts of the 7th-Grade Coursebook ‘English for Nusantara’ - Purwaningtyas, Atika; Sri Wuli Fitriati; Rahayu Puji Haryanti (English Education Journal, 2024)
Cohesion and coherence are critical concepts in the study of reading texts, particularly in the 7th-grade coursebook English for Nusantara, as they directly influence how students understand and engage with the material. This research examined the reading texts in this book, focusing on how cohesive devices contribute to text coherence. By applying a descriptive qualitative approach, the analysis of this study employed the cohesion theory by Halliday and Hasan (2013), whereas the coherence principles applied the theory by Oshima and Hogue (2005). The texts that were analyzed include both descriptive and procedural genres, the focus lay on identifying and analyzing elements of cohesion and coherence present in the textual content. The study found that reference was the most prevalent grammatical cohesion device across both genres, followed by conjunctions, while substitution and ellipsis were absent. Overall, the analysis showed that the reading texts in "English for Nusantara" effectively utilized cohesion and coherence, fulfilling their communicative objectives through the effective application of both grammatical and lexical cohesion devices. The findings of a study on cohesion and coherence in reading texts from the 7th-grade coursebook English for Nusantara can provide valuable insights for improving language teaching, curriculum design, and textbook development in several ways. Also, it can serve as a foundation for developing teaching practices, curricular goals, and textbooks that help students better understand and use cohesion and coherence, ultimately improving their language skills and fostering more effective learning.